Forumet - Matematik C - behöver hjälp.

Matematik C - behöver hjälp.

512 0 4
Homunculi:


Uppgift a)

f(x) = 3x
f(x+h) = 3(x+h)
(f(x+h)-f(x))/h = (3(x+h)-3x)/h
(f(x+h)-f(x))/h = (3x+3h-3x)/h
(f(x+h)-f(x))/h = (3x-3x+3h)/h
(f(x+h)-f(x))/h = 3h/h
(f(x+h)-f(x))/h = 3

Uppgift b)

f(x) = x²-3x+1
f(x+h) = (x+h)²-3(x+h)+1
(f(x+h)-f(x))/h = ((x+h)²-3(x+h)+1-(x²-3x+1))/h
(f(x+h)-f(x))/h = (x²+2xh+h²-3x-3h+1-x²+3x-1)/h
(f(x+h)-f(x))/h = (x²-x²-3x+3x+2xh+h²-3h+1-1)/h
(f(x+h)-f(x))/h = (2xh+h²-3h)/h
(f(x+h)-f(x))/h = 2xh/h+h²/h-3h/h
(f(x+h)-f(x))/h = 2x+h-3
(f(x+h)-f(x))/h = 2x-3+h

Uppgiften nederst

(m, m/s, s)

v(t) = s'(t)
s(t) = t²
v(t) = (t²)'
v(t) = 2t^(2-1)
v(t) = 2t¹
v(t) = 2t
t = 2,5 s
v(2,5 s) = (2*2,5) m/s
v(2,5 s) = 5 m/s
AndersLkpg:

f(x) = x²-3x+1
f(x+h) = (x+h)²-3(x+h)+1
(f(x+h)-f(x))/h = ((x+h)²-3(x+h)+1-(x²-3x+1))/h
(f(x+h)-f(x))/h = (x²+2xh+h²-3x-3h+1-x²+3x-1))/h
(f(x+h)-f(x))/h = (x²-x²-3x+3x+2xh+h²-3h+1-1))/h
(f(x+h)-f(x))/h = (2xh+h²-3h))/h
(f(x+h)-f(x))/h = 2xh/h+h²/h-3h/h
(f(x+h)-f(x))/h = 2x+h-3
(f(x+h)-f(x))/h = 2x-3+h


Hur blev det -3, själv får jag det till +3?

Spana också in: